Interprofessional Student Training: An Evaluation of Teaching Screening, Brief Intervention and Referral to Treatment (SBIRT). Issue 1 (3rd April 2019) - Kobayashi, RIE; Schwartz, Catrina R.; Willson, Megan N.; Clauser, Janelle M.; Mann, Donna P.; Purath, Janet; Davis, April; Hahn, Patricia L.; DePriest, Dawn M.; Tuell, Erica J.; Odom-Maryon, Tamara L.; Bray, Brenda S.; et al.
Abstract : A total of 478 students from 8 disciplines, including social work, participated in an interprofessional education (IPE) Screening, Brief Intervention, and Referral to Treatment (SBIRT) project. A mixed methods evaluation measured student performance and perceptions of the potential impact of the training. Over 90% of student participants indicated that the IPE SBIRT experience laid the foundation for developing interprofessional collaborative care relationships and served as a cornerstone to help understand one's respective role as a member of a health care team. Furthermore, students believed the training enhanced their overall educational experience and interprofessional care would lead to improved patient outcomes.